1976
DOI: 10.1042/bj1560375
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the metabolic role of myo-inositol. Distribution of radioactive myo-inositol in the male rat

Abstract: Radioactive myo-inositol was injected intraperitoneally into nephrectomized rats. The radioactive material present in liver, spleen, brain, heart, diaphragm, seminal vesicle, coagulating gland, prostate, epididymis, vas deferens and testis was shown to consist exclusively of myo-inositol and its derivatives, as shown by paper chromatography of hydrolysates and trichloroacetic acid extracts of these tissues. Radioactive myo-inositol was accumulated rapidly within 1 h by the thyroid, coagulating gland and semina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
34
0

Year Published

1981
1981
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(38 citation statements)
references
References 30 publications
4
34
0
Order By: Relevance
“…Evidence that blood was not the immediate source of luminal inositol in these studies came from the infusion data. Here, as in other studies (Lewin et al, 1976), radioactivity in blood and the epididymis was solely associated with inositol, and in the present study it was shown to enter the lumen. The concentration of [3H]inositol rose much more slowly in the lumen than in blood plasma during the 3-h infusion period, and fell much more slowly after it.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Evidence that blood was not the immediate source of luminal inositol in these studies came from the infusion data. Here, as in other studies (Lewin et al, 1976), radioactivity in blood and the epididymis was solely associated with inositol, and in the present study it was shown to enter the lumen. The concentration of [3H]inositol rose much more slowly in the lumen than in blood plasma during the 3-h infusion period, and fell much more slowly after it.…”
Section: Discussionsupporting
confidence: 67%
“…Previous studies have shown that the rat epididymis can accumulate labelled inositol from blood, but not as actively as do other accessory sex organs (Lewin & Sulimovici, 1975;Lewin et al, 1976): a single injection of tracer produced a stable blood concentration for up to 24 h, and whole epididymal tissue retained higher activity than blood over this period. These differences from the present report reflect differences in technique.…”
Section: Discussionmentioning
confidence: 99%
“…It is not known, however, whether inositol present in the luminal fluid is derived from blood glucose as in the testis or from blood inositol. There is evidence that the rat epididymis contains all the enzymes necessary for the biosynthesis of inositol from glucose (Robinson & Fritz, 1979), although a 12-fold accumulation of blood inositol in the rat epididymis has also been reported (Lewin et al, 1976). Rat epididymal spermatozoa have no ability to synthesize inositol (Eisenberg & Bolden, 1964 (Bedford, 1975;Moore & Bedford, 1978 ;Temple-Smith & Bedford, 1978).…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, it is less certain whether the high concentration of inositol in the epididymis is derived exclusively from the testis or is partly secreted by the epididymal epithelium, although the indirect evidence presently available suggests that inositol may be secreted in the rat epididymis (Lewin et al, 1976; Robinson & Fritz, 1979;Hinton et al, 1980).…”
Section: Introductionmentioning
confidence: 92%
“…In most mammalian cells or tissues. the content of myo-inositol is 5-to 500-fold higher than the level in plasma or extracellular fluid, with active transport system(s) for m-vo-inositol responsible for the maintenance of these concentration gradients (3,4). Whether myo-inositol must be maintained within a critical range in most cells to allow for adequate synthesis of phosphatidylinositol, the most abundant myo-inositol-containing phospholipid, remains to be determined.…”
mentioning
confidence: 99%